Temporary mechanical circulatory support in cardiogenic shock patients after cardiac procedures: selection algorithm and weaning strategies - Nersesian, Gaik; Ott, Sascha; Fardman, Alexander; Lanmueller, Pia; Lewin, Daniel; Bernhardt, Alexander; Emrich, Fabian Christoph; Färber, Gloria; Szabó, Gábor; Oezkur, Mehmet; Panholzer, Bernd; Rojas, Sebastian V.; et al. (Life, 2023)
Mechanical circulatory support has proven effective in managing postcardiotomy cardiogenic shock by stabilizing patients’ hemodynamics and ensuring adequate organ perfusion. Among the available device modalities, the combination of extracorporeal life support and a microaxial flow pump for left ventricular unloading has emerged as a valuable tool in the surgical armamentarium. In this publication, we provide recommendations for the application and weaning of temporary mechanical circulatory support in cardiogenic shock patients, derived from a consensus among leading cardiac centers in German-speaking countries.
Gesehen am 24.05.2024